PERBEDAAN KANDUNGAN 2,Acetyl-1-pyrrolin DAN HASIL BIJI EMPAT KULTIVAR PADI PADA DUA LOKASI TANAM DIFFERENCES OF 2, Acetyl-1-pyrrolin CONTENT AND GRAIN YIELD OF FOUR RICE CULTIVARS AT THE TWO PLANTING LOCATIONS - Dwi Haryanto, Totok Agung (Pembangunan Pedesaan, 2005)
Objective of the research was to study differences of 2,acetyl-1-pyrrolin and grain yield among four upland rice cultivars sowed in two different locations. Randomized block design was applied in the experimental field with three replications. The 2,acetyl-1-pyrrolin content and several agronomic characters were observed. Research result showed that: 1) 2,acetyl-1-pyrrolin content was a stable character and was not differed from locations, 2) grain yield and growth of upland rice sown in Sukoharjo was better than in Cilacap, and 3) Menthikwangi was a favourable cultivar for being cultivated in both Sukoharjo and Cilacap as they gave better yield than other cultivars